Memperkenalkan Makna Perjamuan Kudus Dalam Pandangan Zwingli - Nggebu, Sostenis; Setiyaningsih, Retno; Natanael, Okki; Matheos, Richard Hanny; Legi, Agustinus Hosea (Institut Agama Kristen Negeri Tarutung, 2024)
The problem of this article is the importance of believers understanding Zwingli's view of the meaning of Holy Communion. The purpose of the discussion of this article is to review the understanding of the meaning of Holy Communion according to Zwingli. The method used in this research is literature study. As a result, it reveals that the meaning of Holy Communion in Zwingli's view is to commemorate the great work of Jesus Christ on the cross as well as for people to be united in faith so that they have fellowship with the living God. When receiving the bread and wine of the Holy Communion, people are awakened by their memories of the redemptive work of Jesus Christ on the cross. They imagined that it was Christ who was crucified because of their crimes and sins. Remembering to thank Him, that their salvation is only by the grace of Jesus through His death and resurrection. Even though Christ is not physically present but His presence is received in faith. His presence is to confirm and strengthen them that as God's chosen people they must love one another and keep faith in Him. And, that according to His promise, God will come back to invite people into eternity. Problem dari artikel ini pentingnya orang percaya memahami pandangan Zwingli tentang makna Perjamuan Kudus. Mengingat bahwa pandangan Zwingli tentang makna Perjamuan Kudus terbatas diintrodusir kepada jemaat. Tujuan pembahasan dari artikel ini mengulas pemahaman makna Perjamuan Kudus menurut Zwingli. Metode yang digunakan dalam penelitian ini adalah studi literatur. Hasilnya, mengungkapkan bahwa makna Perjamuan Kudus dalam pandangan Zwingli guna mengenang karya agung Yesus Kristus pada salib sekaligus umat dipersatukan dalam iman agar bersekutu dengan Tuhan yang hidup. Tatkala menyambut roti dan anggur Perjamuan Kudus, umat dibangkitkan ingatan mereka tentang karya penebusan Yesus Kristus pada salib. Mereka membayangkan bahwa Kistus yang tersalib karena kejahatan dan dosa mereka. Mengenang untuk bersyukur kepada-Nya, bahwa keselamatan mereka hanya oleh anugerah Yesus melalui kematian dan kebangkitan-Nya. Sekalipun Kristus tidak hadir secara fisik tetapi kehadiran-Nya diterima dalam iman. Kehadiran-Nya guna meneguhkan dan menguatkan mereka bahwa sebagai umat pilihan Allah mereka mesti saling mengasihi dan tetap beriman kepada-Nya dan menantikan kedatangan-Nya kembali.